A high-efficiency denitrification photocatalyst and its preparation method and application

By combining MnREOx doped cobalt hydrotalcite with g-C3N4, an efficient denitrification catalyst with a wide temperature window is formed, which solves the problem of narrow and easy loss of existing catalysts, significantly improves the removal rate and stability of nitrogen oxides. In complex flue gas environments.

CN119056483BActive Publication Date: 2024-12-27ELEMENT TECH SERVICE (CANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411579050.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2024-12-27
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The active temperature window of existing nitrogen oxide SCR denitrification catalysts is narrow and prone to inactivity, especially in an environment with water and sulfur, which shows toxic effects, resulting in poor denitrification effect.

Method used

Using a combined catalyst of MnREOx doped cobalt hydrotalcite and g-C3N4, a high-efficiency denitrification catalyst with wide temperature window and high catalytic activity is formed through metal oxide doping modification and hydrothermal reaction, thereby enhancing the water resistance and light of the catalyst. Catalytic properties.

Benefits of technology

It achieves the maintenance of efficient denitrification performance over a wider temperature range, improves the stability of the catalyst and water and sulfur resistance, and significantly improves the removal rate of nitrogen oxides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119056483B_ABST
    Figure CN119056483B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of catalyst materials, and in particular to a highly efficient denitration photocatalyst and a preparation method and application thereof. The highly efficient denitration photocatalyst is MnREO x Doped cobalt-iron hydrotalcite / g-C3N4, wherein RE is any one of La, Ce or Yb. The present invention utilizes the synergistic effect of metal oxide-doped cobalt-iron hydrotalcite and g-C3N4 to obtain a SCR denitration photocatalyst with stability and a wide active temperature window. The technical solution of the present invention effectively solves the problem that the catalyst used in the prior art for SCR denitration of nitrogen oxides has a narrow active temperature window and is easy to lose activity, providing a new idea for SCR denitration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst materials, and in particular to a high-efficiency denitration photocatalyst and a preparation method and application thereof. Background Art

[0002] Nitrogen oxides (NO x ) is one of the main air pollutants, mainly including nitric oxide and nitrogen dioxide. The large-scale emission of nitrogen oxides will cause serious environmental problems such as photochemical smog, nitric acid rain and ozone layer depletion, and cause certain toxic effects on organisms. Therefore, reducing the emission of nitrogen oxides is an important environmental protection task that needs to be solved urgently.

[0003] In order to effectively control the emission of nitrogen oxides, tail gas denitrification is generally adopted. The existing tail gas denitrification methods include SNCR denitrification, SCR denitrification or a combination of the two. Among them, SCR denitrification is the process in which nitrogen oxides and ammonia in flue gas are converted into water and nitrogen dioxide under the catalytic action of denitrification catalysts. Since SCR denitrification has the advantages of high denitrification activity, long chemical life, low ammonia escape rate, and low sulfur dioxide oxidation rate, it is widely used in industrial kiln / boiler tail gas denitrification. However, the catalyst currently used in SCR denitrification has a narrow active temperature window and is easily poisoned by sulfur dioxide molecules under water and sulfur-containing working conditions, thereby losing its activity.

[0004] Based on this, the development of a highly active and stable denitrification catalyst has important practical significance for the denitrification treatment of nitrogen oxides. Summary of the invention

[0005] In view of the problem that the catalyst used in the prior art for SCR denitration of nitrogen oxides has a narrow active temperature window and is easily deactivated, the present invention provides a highly efficient denitration photocatalyst and its preparation method and application. The highly efficient denitration photocatalyst is MnREO x Doped cobalt-iron hydrotalcite / g-C3N4, a SCR denitrification photocatalyst with stability and a wide active temperature window was obtained by utilizing the combination of metal oxide-doped cobalt-iron hydrotalcite and g-C3N4.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a high-efficiency denitration photocatalyst, wherein the high-efficiency denitration photocatalyst is MnREO x Cobalt-doped iron hydrotalcite / g-C3N4, wherein RE is any one of La, Ce or Yb.

[0008] Compared with the prior art, the present invention first performs a metal oxide doping modification treatment on the cobalt-iron hydrotalcite. The surface of the manganese oxide is distributed with hydrophilic hydroxyl groups, and water is more likely to combine with the surface hydroxyl groups. Therefore, the presence of manganese oxide will weaken the interference of water on the photocatalyst, ensuring that the photocatalyst has good water resistance in a complex flue gas environment. The incorporation of rare earth oxides has a certain effect on the structure of the hydrotalcite, resulting in an increase in its specific surface area, a decrease in pore size, an increase in pore volume, and more catalytic active sites exposed. At the same time, manganese oxide and rare earth oxide will cause an increase in the weak acid sites of the photocatalyst, making it easier to adsorb a large amount of nitrogen oxides, ensuring that the catalyst has a higher catalytic effect in a wider temperature range.

[0009] There is a co-catalytic effect between g-C3N4 and cobalt iron hydrotalcite. Since the surface of cobalt iron hydrotalcite has manganese oxide rich in hydroxyl groups, high concentrations of hydroxyl groups will promote the formation of carbon vacancies in g-C3N4, while building interfacial chemical bonds between g-C3N4 and cobalt iron hydrotalcite, promoting the effective separation and migration of photogenerated electrons and holes in the catalyst, and improving the photocatalytic performance of the catalyst. In addition, since g-C3N4 has a high specific surface area and high light capture rate, it can provide more active oxygen for the photocatalyst, further improving the efficiency of photocatalytic degradation of nitrogen oxides.

[0010] The second aspect of the present invention provides a method for preparing the highly efficient denitration photocatalyst, comprising the following steps:

[0011] Step 1: Evenly mix the manganese source, RE source, cobalt source and iron source, and dissolve them in deionized water to obtain a metal salt solution;

[0012] Step 2: Adjust the pH of the metal salt solution to 8-9, stir at 70-90°C, separate the solid and liquid, wash, and dry to obtain a precursor; heat-treat the precursor at 280-350°C to obtain MnREO x Cobalt-doped iron hydrotalcite;

[0013] Step 3: Grind the melamine, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 500-550°C in an inert atmosphere for calcination, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tube furnace, and sinter it at 450-500°C to obtain g-C3N4;

[0014] Step 4: Mix the g-C3N4 and the MnREO x The cobalt-iron doped hydrotalcite is dispersed in organic alcohol, and hydrothermally reacted at 120-140° C. in an inert atmosphere, filtered, washed, and dried to obtain a highly efficient denitration photocatalyst.

[0015] Preferably, in step 1, the manganese source is any one of manganese nitrate, manganese chloride or manganese sulfate.

[0016] Preferably, the RE source is any one of lanthanum nitrate, cerium nitrate or ytterbium nitrate.

[0017] Preferably, the cobalt source is any one of cobalt nitrate or cobalt chloride.

[0018] Preferably, the iron source is any one of ferric chloride or ferric nitrate.

[0019] Preferably, in step 1, the molar ratio of the manganese source, RE source, cobalt source and iron source is 0.3:(0.05-0.1):1:1.

[0020] In step 1, the mass volume ratio of the total solid amount of the manganese source, RE source, cobalt source and iron source to deionized water is 1g:2mL-1g:4mL.

[0021] Preferably, in step 2, the stirring treatment time is 50-80 minutes.

[0022] Preferably, in step 2, the heat preservation treatment time is 2-4 hours.

[0023] Preferably, in step three, the grinding time is 25-40 min.

[0024] Preferably, in step three, the temperature is raised to 500-550° C. by programmed heating, with a heating rate of 15-25° C. / min.

[0025] Preferably, in step three, the calcination time is 3-6 hours.

[0026] Preferably, in step three, the temperature is raised to 450-500° C. by programmed heating, with a heating rate of 10-15° C. / min.

[0027] Preferably, in step three, the sintering time is 2-3 hours.

[0028] Preferably, in step 4, the g-C3N4 and the MnREO x The mass ratio of the cobalt-iron doped hydrotalcite is 0.4:1-0.7:1.

[0029] Preferably, in step 4, the MnREO x The mass volume ratio of the cobalt-doped iron hydrotalcite to the organic alcohol is 1g:3mL-1g:5mL.

[0030] Preferably, in step 4, the organic alcohol is ethylene glycol.

[0031] Preferably, in step 4, the hydrothermal reaction time is 4-6 hours.

[0032] The third aspect of the present invention provides an application of the high-efficiency denitration photocatalyst in flue gas denitration.

[0033] Preferably, the working temperature of the high-efficiency denitration photocatalyst is 300-450°C.

[0034] In summary, the present invention provides a highly efficient denitration photocatalyst and its preparation method and application, wherein the highly efficient denitration photocatalyst is MnREO x Doped cobalt iron hydrotalcite / g-C3N4, using the combination of metal oxide doped cobalt iron hydrotalcite and g-C3N4, a SCR denitration photocatalyst with stability and a wide active temperature window is obtained. The present invention effectively solves the problem that the catalyst used in the prior art for nitrogen oxide SCR denitration treatment has a narrow active temperature window and is easy to lose activity, and provides a new idea for SCR denitration. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the NO removal effect of the denitration photocatalysts obtained in Example 1 and Comparative Examples 1-4 at 250° C.-500° C.;

[0036] Figure 2 Schematic diagram of the NO removal effect of the denitration photocatalysts obtained in Example 1 and Comparative Examples 1-4 under water and sulfur resistance conditions. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment provides a highly efficient denitrification photocatalyst MnLaO x Doped cobalt-iron hydrotalcite / g-C3N4, specifically including the following contents:

[0040] Step 1: Evenly mix 5.37 g manganese nitrate, 4.68 g lanthanum nitrate, 29.10 g cobalt nitrate and 24.19 g ferric nitrate, and dissolve them in 150 mL deionized water to obtain a metal salt solution;

[0041] Step 2: Adjust the pH of the metal salt solution to 8.2, stir at 85°C for 60 minutes, separate the solid and liquid, wash with deionized water 3 times, and dry at 80°C for 24 hours to obtain a precursor; heat the precursor at 330°C for 3 hours to obtain MnLaOx Cobalt-doped iron hydrotalcite;

[0042] Step 3: Grind 30 g of melamine for 30 min, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 520 ° C at a heating rate of 20 ° C / min in an inert atmosphere, calcine it for 5 h, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tubular furnace, heat it to 480 ° C at a heating rate of 12 ° C / min, sinter it for 2.5 h, and obtain g-C3N4;

[0043] Step 4: Mix 20g of the g-C3N4 and 45g of the MnLaO x The cobalt-doped iron hydrotalcite was dispersed in 150 mL of ethylene glycol, and subjected to hydrothermal reaction at 130 °C for 5 h under an inert atmosphere. The mixture was filtered, washed with deionized water three times, and dried at 120 °C for 10 h to obtain MnLaO x Cobalt-doped iron hydrotalcite / g-C3N4.

[0044] Example 2

[0045] This embodiment provides a highly efficient denitrification photocatalyst MnCeO x Doped cobalt-iron hydrotalcite / g-C3N4, specifically including the following contents:

[0046] Step 1: Evenly mix 5.37 g manganese nitrate, 3.91 g cerium nitrate, 29.10 g cobalt nitrate and 24.19 g ferric nitrate, and dissolve them in 150 mL deionized water to obtain a metal salt solution;

[0047] Step 2: Adjust the pH of the metal salt solution to 8.5, stir at 80°C for 70 min, separate the solid and liquid, wash with deionized water 3 times, and dry at 80°C for 24 h to obtain a precursor; heat-treat the precursor at 350°C for 2 h to obtain MnCeO x Cobalt-doped iron hydrotalcite;

[0048] Step 3: Grind 30 g of melamine for 30 min, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 540 ° C at a heating rate of 15 ° C / min in an inert atmosphere, calcine it for 5 h, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tubular furnace, heat it to 450 ° C at a heating rate of 15 ° C / min, sinter it for 3 h, and obtain g-C3N4;

[0049] Step 4: Mix 20g of the g-C3N4 and 45g of the MnCeO xThe cobalt-doped iron hydrotalcite was dispersed in 150 mL of ethylene glycol, and hydrothermally reacted at 135 °C for 4 h under an inert atmosphere, filtered, washed with deionized water three times, and dried at 120 °C for 10 h to obtain MnCeO x Cobalt-doped iron hydrotalcite / g-C3N4.

[0050] Example 3

[0051] This embodiment provides a highly efficient denitrification photocatalyst MnYbO x Doped cobalt-iron hydrotalcite / g-C3N4, specifically including the following contents:

[0052] Step 1: Evenly mix 5.37 g of manganese nitrate, 3.59 g of ytterbium nitrate, 29.10 g of cobalt nitrate and 24.19 g of ferric nitrate, and dissolve them in 150 mL of deionized water to obtain a metal salt solution;

[0053] Step 2: Adjust the pH of the metal salt solution to 9.0, stir at 90°C for 50 min, separate the solid and liquid, wash with deionized water 3 times, and dry at 80°C for 24 h to obtain a precursor; heat-treat the precursor at 300°C for 4 h to obtain MnYbO x Cobalt-doped iron hydrotalcite;

[0054] Step 3: Grind 30 g of melamine for 30 min, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 550 ° C at a heating rate of 25 ° C / min in an inert atmosphere, calcine it for 5 h, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tubular furnace, heat it to 500 ° C at a heating rate of 10 ° C / min, sinter it for 2 h, and obtain g-C3N4;

[0055] Step 4: Mix 20g of the g-C3N4 and 45g of the MnYbO x The cobalt-doped iron hydrotalcite was dispersed in 150 mL of ethylene glycol, and subjected to hydrothermal reaction at 125 °C for 6 h under an inert atmosphere. The mixture was filtered, washed with deionized water three times, and dried at 120 °C for 10 h to obtain MnYbO x Cobalt-doped iron hydrotalcite / g-C3N4.

[0056] Comparative Example 1

[0057] This comparative example provides a denitration photocatalyst MnLaO x Cobalt-iron doped hydrotalcite, specifically including the following contents:

[0058] Step 1: Evenly mix 5.37 g manganese nitrate, 4.68 g lanthanum nitrate, 29.10 g cobalt nitrate and 24.19 g ferric nitrate, and dissolve them in 150 mL deionized water to obtain a metal salt solution;

[0059] Step 2: Adjust the pH of the metal salt solution to 8.2, stir at 85°C for 60 minutes, separate the solid and liquid, wash with deionized water 3 times, and dry at 80°C for 24 hours to obtain a precursor; heat the precursor at 330°C for 3 hours to obtain MnLaO x Cobalt-doped iron hydrotalcite.

[0060] Comparative Example 2

[0061] This comparative example provides a denitration photocatalyst cobalt iron hydrotalcite / g-C3N4, which specifically includes the following contents:

[0062] Step 1: Mix 29.10 g of cobalt nitrate and 24.19 g of ferric nitrate evenly, and dissolve them in 150 mL of deionized water to obtain a metal salt solution;

[0063] Step 2: adjusting the pH of the metal salt solution to 8.2, stirring the solution at 85° C. for 60 min, separating the solid from the liquid, washing with deionized water for 3 times, and drying the solution at 80° C. for 24 h to obtain a precursor; heat-treating the precursor at 330° C. for 3 h to obtain cobalt-iron hydrotalcite;

[0064] Step 3: Grind 30 g of melamine for 30 min, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 520 ° C at a heating rate of 20 ° C / min in an inert atmosphere, calcine it for 5 h, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tubular furnace, heat it to 480 ° C at a heating rate of 12 ° C / min, sinter it for 2.5 h, and obtain g-C3N4;

[0065] Step 4: Disperse 20 g of the g-C3N4 and 45 g of the cobalt-iron hydrotalcite in 150 mL of ethylene glycol, carry out hydrothermal reaction at 130°C for 5 h under an inert atmosphere, filter, wash with deionized water 3 times, and dry at 120°C for 10 h to obtain cobalt-iron hydrotalcite / g-C3N4.

[0066] Comparative Example 3

[0067] This comparative example provides a denitration photocatalyst MnO x Doped cobalt-iron hydrotalcite / g-C3N4, specifically including the following contents:

[0068] Step 1: Evenly mix 5.37 g manganese nitrate, 29.10 g cobalt nitrate and 24.19 g ferric nitrate, and dissolve them in 150 mL deionized water to obtain a metal salt solution;

[0069] Step 2: Adjust the pH of the metal salt solution to 8.2, stir at 85°C for 60 min, separate the solid and liquid, wash with deionized water 3 times, and dry at 80°C for 24 h to obtain a precursor; heat-treat the precursor at 330°C for 3 h to obtain MnO x Cobalt-doped iron hydrotalcite;

[0070] Step 3: Grind 30 g of melamine for 30 min, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 520 ° C at a heating rate of 20 ° C / min in an inert atmosphere, calcine it for 5 h, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tubular furnace, heat it to 480 ° C at a heating rate of 12 ° C / min, sinter it for 2.5 h, and obtain g-C3N4;

[0071] Step 4: Mix 20g of the g-C3N4 and 45g of the MnO x The cobalt-doped iron hydrotalcite was dispersed in 150 mL of ethylene glycol, and subjected to hydrothermal reaction at 130 °C for 5 h under an inert atmosphere. The mixture was filtered, washed with deionized water three times, and dried at 120 °C for 10 h to obtain MnO x Cobalt-doped iron hydrotalcite / g-C3N4.

[0072] Comparative Example 4

[0073] This comparative example provides a denitration photocatalyst MnLaO x Doped zinc-aluminum hydrotalcite / g-C3N4, specifically including the following contents:

[0074] Step 1: Evenly mix 5.37 g manganese nitrate, 4.68 g lanthanum nitrate, 29.75 g zinc nitrate and 37.51 g aluminum nitrate, and dissolve them in 150 mL deionized water to obtain a metal salt solution;

[0075] Step 2: Adjust the pH of the metal salt solution to 8.2, stir at 85°C for 60 minutes, separate the solid and liquid, wash with deionized water 3 times, and dry at 80°C for 24 hours to obtain a precursor; heat the precursor at 330°C for 3 hours to obtain MnLaO x Doped zinc-aluminum hydrotalcite;

[0076] Step 3: Grind 30 g of melamine for 30 min, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 520 ° C at a heating rate of 20 ° C / min in an inert atmosphere, calcine it for 5 h, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tubular furnace, heat it to 480 ° C at a heating rate of 12 ° C / min, sinter it for 2.5 h, and obtain g-C3N4;

[0077] Step 4: Mix 20g of the g-C3N4 and 45g of the MnLaO x The doped zinc-aluminum hydrotalcite was dispersed in 150 mL of ethylene glycol, and subjected to hydrothermal reaction at 130 °C for 5 h under an inert atmosphere, filtered, washed with deionized water three times, and dried at 120 °C for 10 h to obtain MnLaO x Doped ZnAl-HD / g-C3N4.

[0078] In order to further reflect the technical effect of the present invention, the present invention has carried out relevant performance tests on the denitration photocatalysts obtained in Example 1 and Comparative Examples 1-4, specifically including the following contents: a denitration activity test is carried out in a fixed bed reactor, equipped with an H-type 350W ultraviolet lamp or mercury lamp, and a Halpu HPWF51 catalytic evaluation device. During the catalyst denitration activity detection, the flow rate is adjusted so that the gas concentration in the reaction tube satisfies the NO volume fraction of 0.03%, the NH3 volume fraction of 0.03%, and the O2 volume fraction of 16%, and the remaining gas is balanced with N2. The amount of catalyst particles added to the reactor is 1g, the mixed gas flow rate is 280mL / min, and the reaction volume space velocity is 50000h -1 The test temperature is 250-500℃, and the temperature is kept at 50℃ for 1h. The temperature of the reaction process is controlled by the heating furnace program.

[0079] When testing the H2O resistance performance, after the catalyst is stabilized at 350°C, introduce 10% volume fraction of water vapor and maintain it for 3 hours. Then introduce 100 ppm of SO2. Keep introducing water vapor and SO2. After maintaining it for 1.5 hours, stop introducing water vapor. After maintaining it for 0.5 hours, stop introducing SO2. Maintain it for 1 hour and end the test.

[0080] The calculation formula of NO removal rate is as follows: NO removal rate (%) = (NO inlet-NO outlet) / NO inlet × 100%; the results are shown in Table 1-2 and Figure 1-2 shown.

[0081] Table 1 NO removal rate of denitration photocatalysts obtained in Example 1 and Comparative Examples 1-4 at 250°C-500°C

[0082]

[0083] Table 2 NO removal rate of denitration photocatalysts obtained in Example 1 and Comparative Examples 1-4 under water and sulfur resistance conditions

[0084]

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly efficient denitrification photocatalyst, characterized by: The high-efficiency denitrification photocatalyst is MnREO x Cobalt-doped iron hydrotalcite / g-C3N4, wherein RE is any one of La, Ce or Yb; The preparation method of the high-efficiency denitration photocatalyst comprises the following steps: Step 1: Evenly mix the manganese source, RE source, cobalt source and iron source, and dissolve them in deionized water to obtain a metal salt solution; Step 2: Adjust the pH of the metal salt solution to 8-9, stir at 70-90°C, separate the solid and liquid, wash, and dry to obtain a precursor; heat-treat the precursor at 280-350°C to obtain MnREO x Cobalt-doped iron hydrotalcite; Step 3: Grind the melamine, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 500-550°C in an inert atmosphere for calcination, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tube furnace, and sinter it at 450-500°C to obtain g-C3N4; Step 4: Mix the g-C3N4 and the MnREO x The cobalt-iron doped hydrotalcite is dispersed in an organic alcohol, and a hydrothermal reaction is carried out at 120-140°C in an inert atmosphere, and then filtered, washed and dried to obtain a highly efficient denitration photocatalyst; In step 4, the organic alcohol is ethylene glycol; In step 4, the hydrothermal reaction time is 4-6 hours.

2. The method for preparing a highly efficient denitration photocatalyst according to claim 1, characterized in that: The steps include: Step 1: Evenly mix the manganese source, RE source, cobalt source and iron source, and dissolve them in deionized water to obtain a metal salt solution; Step 2: Adjust the pH of the metal salt solution to 8-9, stir at 70-90°C, separate the solid and liquid, wash, and dry to obtain a precursor; heat-treat the precursor at 280-350°C to obtain MnREO x Cobalt-doped iron hydrotalcite; Step 3: Grind the melamine, place the ground melamine in a crucible, seal it with aluminum foil, heat it to 500-550°C in an inert atmosphere for calcination, and cool it to obtain graphite carbon nitride; remove the aluminum foil, transfer the crucible to a tube furnace, and sinter it at 450-500°C to obtain g-C3N4; Step 4: Mix the g-C3N4 and the MnREO x The cobalt-iron doped hydrotalcite is dispersed in an organic alcohol, and a hydrothermal reaction is carried out at 120-140°C in an inert atmosphere, and then filtered, washed and dried to obtain a highly efficient denitration photocatalyst; In step 4, the organic alcohol is ethylene glycol; In step 4, the hydrothermal reaction time is 4-6 hours.

3. The method for preparing a highly efficient denitration photocatalyst according to claim 2, characterized in that: In step 1, the manganese source is any one of manganese nitrate, manganese chloride or manganese sulfate; and / or The RE source is any one of lanthanum nitrate, cerium nitrate or ytterbium nitrate; and / or The cobalt source is any one of cobalt nitrate or cobalt chloride; and / or The iron source is any one of ferric chloride or ferric nitrate.

4. The method for preparing a highly efficient denitration photocatalyst according to claim 2, characterized in that: In step 1, the molar ratio of the manganese source, RE source, cobalt source and iron source is 0.3:(0.05-0.1):1:1; and / or In step 1, the mass volume ratio of the total solid amount of the manganese source, RE source, cobalt source and iron source to deionized water is 1g:2mL-1g:4mL; and / or In step 2, the stirring time is 50-80 min; and / or In step 2, the heat preservation treatment time is 2-4 hours.

5. The method for preparing a highly efficient denitration photocatalyst according to claim 2, characterized in that: In step 3, the grinding time is 25-40 min; and / or In step 3, the temperature is raised to 500-550°C by programmed heating at a heating rate of 15-25°C / min; and / or In step 3, the calcination time is 3-6 hours.

6. The method for preparing a highly efficient denitration photocatalyst according to claim 2, characterized in that: In step 3, the temperature is raised to 450-500°C by programmed heating at a heating rate of 10-15°C / min; and / or In step three, the sintering time is 2-3 hours.

7. The method for preparing a highly efficient denitration photocatalyst according to claim 2, characterized in that: In step 4, the g-C3N4 and the MnREO x The mass ratio of the cobalt-iron hydrotalcite doped is 0.4:1-0.7:1; and / or In step 4, the MnREO x The mass volume ratio of the cobalt-doped iron hydrotalcite to the organic alcohol is 1g:3mL-1g:5mL.

8. Use of the high-efficiency denitration photocatalyst as claimed in claim 1 in flue gas denitration.

9. The use of the high-efficiency denitration photocatalyst in flue gas denitration as claimed in claim 8, characterized in that: The working temperature of the high-efficiency denitration photocatalyst is 300-450°C.

Citation Information

Patent Citations

  • Preparation method for WO3-LDH composite film for photoelectrocatalytic water decomposition

    CN106222685A

  • Preparation method of porous carbon nitride foam / hydrotalcite three-dimensional hetero-junction material and application thereof in photo catalytic reduction of carbon dioxide

    CN114011447A